The Relationship Between Burnout, Stress, And Resilience Among Vietnamese Health Care Workers - Nguyen, Vu Hoang Anh; Phan, Yen Thi Hoai; Vuong, Thien Nguyen Toan; Truong, Ngoc-Anh; Le, Tin Duc; Nguyen, Xuan Thanh Kieu; Tran-Chi, Vinh-Long (National Journal of Community Medicine, 2024)
Introduction: The COVID-19 pandemic has also caused significant damage in Vietnam, necessitating medical personnel to work tirelessly at different medical establishments to combat the epidemic. Healthcare professionals in Vietnam may experience stress and burnout, leading to adverse effects on their resilience, job performance, health, and overall quality of life. Methodology: We carried out a cross-sectional investigation involving 147 healthcare professionals from various medical establishments in Ho Chi Minh City, Vietnam. The purpose was to evaluate the levels of stress, burnout, and resilience among these individuals. Results: The study discovered that resilience acts as a mediator in the association between stress and burnout. Additionally, it revealed that gender traits have an impact on the interplay between stress and mental resilience. The study additionally discovered inequalities in stress, burnout, resilience, and social support based on demographic and professional factors. Conclusion: Our study has enhanced our comprehension of mental health concerns among healthcare workers and facilitated the identification of a complex pattern that takes into account detrimental factors, protective factors, and existing support systems in mental healthcare, thus offering comprehensive and insightful perspectives for future research.